Smooth Sailing: A Pilot Study of an Online, School-Based, Mental Health Service for Depression and Anxiety - O’Dea, Bridianne; King, Catherine; Subotic-Kerry, Mirjana; Achilles, Melinda Rose; Cockayne, Nicole; Christensen, Helen (Frontiers in Psychiatry, 2019)
Background: Schools play an important role in supporting young people’s mental health, but face challenges identifying and responding to students in need of care. To assist secondary schools, the Black Dog Institute has developed an online, schools-based, mental health service (Smooth Sailing). Delivered in the classroom, Smooth Sailing uses a website to screen, assess, allocate, and deliver care for depression and anxiety. The service is based on the principles of stepped care, offering treatments with varied intensity and follow-up by a school counsellor when necessary. The current study aimed to evaluate the feasibility, acceptability, and safety of this new type of service among secondary school students. Methods: Between February and June 2017, a single-arm, pre-post, pilot study was conducted among students from four NSW secondary schools. Schools were given access to the service for 6-weeks. Feasibility measures (consent rates and step allocations), acceptability measures (service use and satisfaction) and safety measures (deterioration in help-seeking intention scores and mental health symptoms) were assessed at baseline and completion of the 6-week trial period. Results: A total of 59 students took part in the service pilot (Mean age: 14.57, SD: 0.89, range: 13-16). At baseline, 18.6% of students were found to require follow-up from the school counsellor and 4 out of 5 were new cases. Although completion of the online modules was low, service satisfaction was high. At 6-weeks, the mean scores for help-seeking, depression and anxiety remained relatively stable or improved. Conclusions: The current study presents important findings for the development and implementation of an online mental health service that screens students’ mental health and allocates care accordingly, all within the school setting. While the findings provide some support for feasibility, acceptability, and safety, service improvements are needed. The modifications outlined are likely to improve the quality of the service and its effectiveness.